The Improvement of Broiler Performance with Modification of Particle Size and Palm Kernel Meal Levels - Setiana, I.; Nahrowi; Sumiati; Subekti, S. (Faculty of Animal Science, IPB University, 2025)
Palm kernel meal (PKM) is a by-product of palm oil production and can be used as an energy source in broiler feed. However, the utilization of PKM in broiler feed has yet to be optimal due to its low nutrient digestibility. This study aims to evaluate the particle size and the levels of PKM in the feed to increase broiler performance. The particle sizes used in this study were 2.5 and 1 mm, and the levels were 5%, 10%, and 15%. An in vivo study was conducted using 1,440 Ross 308 broilers day 0-35, with an average initial weight of 47 grams. The study employed a completely randomized factorial design of 2x3, divided into 6 treatments consisting of (T1) 2.5 mm at 5% PKM as a control, (T2) 1 mm at 5% PKM, (T3) 2.5 mm at 10% PKM, (T4) 1 mm at 10% PKM, (T5) 2.5 mm at 15% PKM, and (T6) 1 mm at 15% PKM on feed. The studied variables were body weight (BW), feed intake (FI), feed conversion ratio (FCR), European production efficiency factor (EPEF), and carcass quality. Increasing PKM levels decreased the pellet durability index of broiler feed. During the starter stage (days 0-21), 1 mm PKM significantly improved FCR (p<0.05) compared to 2.5 mm, although PKM levels did not significantly affect broiler performances. In the finisher stage (days 22-35), 15% of PKM levels negatively impacted FCR and EPEF. Overall, from 0-35 days of age, the best broiler performances showed by treatment T2 with 1 mm particle size and 5% PKM.